Inhibition of adenovirus transport from the endosome to the cell nucleus by rotenone - Balsera-Manzanero, María; Ghirga, Francesca; Ruiz-Molina, Ana; Mori, Mattia; Pachón, Jerónimo; Botta, Bruno; Cordero, Elisa; Quaglio, Deborah; Sánchez-Céspedes, Javier (Frontiers in Pharmacology, 2024)
Regardless of the clinical impact of human adenovirus (HAdV) infections in the healthy population and its high morbidity in immunosuppressed patients, a specific treatment isstill not yet available. In this study, we screened the CM1407 COST Action's chemical library, comprising 1,233 natural products to identify compounds that restrict HAdV infection. Among them, we identified rotenolone, a compound that significantly inhibited HAdV infection. Next, we selected four isoflavonoid-type compounds (e.g., rotenone, deguelin, millettone, and tephrosin), namely rotenoids, structurally related to rotenolone in order to evaluate and characterized in vitro their antiviral activities against HAdV and human cytomegalovirus (HCMV). Their IC50 values for HAdV ranged from 0.0039 µM for rotenone to 0.07 µM for tephrosin, with selective indices ranging from 164.1 for rotenone to 2,429.3 for deguelin. In addition, the inhibition of HCMV replication ranged from 50% to 92.1% at twice the IC50 concentrations obtained in the plaque assay for each compound against HAdV. Our results indicated that the mechanisms of action of rotenolone, deguelin, and tephrosin involve the late stages of the HAdV replication cycle.However, the antiviral mechanism of action of rotenone appears to involve the alteration of the microtubular polymerization, which prevents HAdV particles from reaching the nuclear membrane of the cell. These isoflavonoid-type compounds exert high antiviral activity against HAdV at nanomolar concentrations, and can be considered strong hit candidates for the development of a new class of broad-spectrum antiviral drugs.